Enantioselective divergent total syntheses of fawcettimine-type Lycopodium alkaloids. Issue 1 (7th January 2015) - Zeng, Chen; Zhao, Jingyun; Zhao, Gang
Abstract Enantioselective divergent total syntheses of (+)-fawcettimine, (+)-fawcettidine, (+)-lycoflexine, (+)-lycoposerramine Q, (−)-Huperzine Q and (+)-N-oxyhuperzine Q have been described from a common precursor. The syntheses feature a vinylogous Rubottom oxidation and several biomimetic transformations.